Você está na página 1de 2

SMA332 – C´alculo II

Primeira Lista 16 de agosto de 2011

f

a) f(x, y) =

xy

x

2y

b) f(u, v) = 1 u e u/v

c) f(x, y) =

xy x 2 y 3

z = f(x, y)

x + y 1 + z 2 = 0, z 0 x y

z =

1 x 2 y 2

z = (2x 2 + y 2 1)

z 2 + 4 = x 2 + y 2 , z 0

z =

4x 2 + y 2 + z 2 = 1, z 0

|x| |y|

f(x, y) = x 2 + 2xy c f c = 0 c ̸= 0 f y = mx m R f

a) f(x, y) = x y

c)

f(x, y) = x 2 + y 2

4

e) f(x, y) = x 2 + y 2

g)

i) f(x, y) = 1 x 2 y 2

k) f(x, y) = 1 x 2 , x 0, y 0 e x + y 1

f(x, y) = 1 x 2 y 2

b) f(x, y) = e x

2y

d) f(x, y) = x + y

f) f(x, y) =

1

x 2 + y 2

h) f(x, y) = x + y + 1

j) f(x, y) = x 2 , 1 x 0 e y 0

l) f(x, y) = xy

a)

f(x, y, z) = x,

c = 1

c)

f(x, y, z)

= x 2 + y 2 , c = 1

 

e)

f(x, y, z) = x y, c = 0, 1, 2

g)

f(x, y, z) = x 2 + y 2 + z 2 , c = −1, 0, 2

b) f(x, y, z) = y, c = 1

d) f(x, y, z) = x 2 + 4y 2 + z 2 , c = 1

f) f(x, y, z) = x 2 + y 2

4

2

+ z

9

, c = 0, 1, 2

h) f(x, y, z) = xy, c = 0, 1, 2

γ (t).

γ(t) = (1, t, 1),

t R

γ(t) = (1, 1, t),

t 0

γ(t) = (t, t, 1), t 0

γ(t) = ( t, t, 2)

γ(t) = (t, t, 1 + t), t 0

SMA332 – C´alculo II

Primeira Lista 16 de agosto de 2011

γ(t) = ( 1, 1, 1 t ) , t > 0

γ(t) = ( t, t, e t ), t 0

γ(t) = (1 + t, 1 + t, t), π

γ(t) = (e t t, e t t), t 0

2

t π

2

a)

(x,y)(0,0)

e 1/(x 2 +y 2 )

d)

g)

j)

(x,y)(0,0) x 2 y

x

(x,y)(0,0)

(x,y)(0,0)

1 + x y

x 2 + y 2

x 2 y

x 4 + y 2

m)

p)

(x,y)(0,0)

xy

x 2

+ y 2

(x,y)(0,0) x

1

x 2 + y 2

b)

e)

h)

k)

n)

q)

(x,y)(0,0)

x 2 y 2

1 + x 2 + y 2

(x,y)(0,0) (x 2 + y 2 )

1

xy

(x,y)(0,0) (1 + y 2 ) x

x

(x,y)(0,0) (x

3 + 2x 2 y y 2 + 2)

(x,y)(0,0)

4 + 3x 2 y 2 + 2xy 3 (x 2 + y 2 ) 2

x

(x,y)(0,0)

x

+ y

x

y

c)

f)

i)

l)

o)

r)

(x,y)(0,0)

x

x 2 + y 2

(x,y)(0,0)

x 2 y 2 x 2 y 2 + (x y) 2

(x,y,z)(0,0,0)

4x y 3z

2x 5y + 2z

(x,y)(0,0)

(x,y)(0,0)

e x + e y

x + y

x 2 y 2 |x 3 | + |y 3 |

(x,y)(0,0)

xy y x 3

(h,k)(0,0)

f(x + h, y + k) − f(x, y) − 2xh k

h 2 + k 2

f(x, y) = x 2 + y

(h,k)(0,0)

f(h, k)

(h,

k) f f(x, y) =

x

3

x 2 + y 2

(h, k)= h 2 + k 2 .

a)

c)

f(x, y) =

f(x, y) =

x 3y x 2 + y

0,

2 ,

2

xy + y 2 ,

x 2

0,

(x, y) ̸= (0, 0)

(x, y) = (0, 0)

(x, y) ̸= (0, 0)

(x, y) = (0, 0)

b)

d)

f(x, y) =

f(x, y) =

(x 2 + y 2 ) x 2 + y 2

1,

,

(x, y) ̸= (0, 0)

(x, y) = (0, 0)

x

3

2

x

0,

+ y 2 ,

(x, y) ̸= (0, 0)

(x, y) = (0, 0)

A R 2 (x 0 , y 0 ) (x 1 , y 1 ) A

f

< m < f(x 1 , y 1 ) (x, y) A f(x, y) = m

A f(x 0 , y 0 )

γ : [a, b] A γ(a) = (x 0 , y 0 ) γ(b) = (x 1 , y 1 )

g(t) = f(γ(t)) t [a, b]